Introductory Mathematics for Economics and Business / Second Edition - Holden K; Macmillan (Pearson Addison-Wesley, 1994)
This book covers the essential mathematics required by students of economics and business. Preface, Linear Equations, Elementary Matrix Algebra, Non-Linear Equations, Series, Differential Calculus, Integral Calculus, Partial Differentiation, Linear Programming, Differential Equations, Difference Equations, Appendices, Further Reading, Index.